2015
DOI: 10.1186/s12887-015-0447-z
|View full text |Cite
|
Sign up to set email alerts
|

Children’s perceptions about medicines: individual differences and taste

Abstract: BackgroundBitter taste receptors are genetically diverse, so children likely vary in sensitivity to the “bad” taste of some pediatric formulations. Based on prior results that variation in a bitter taste receptor gene, TAS2R38, was related to solid (pill) formulation usage, we investigated whether this variation related to liquid formulation usage and young children’s reports of past experiences with medicines and whether maternal reports of these past experiences were concordant with those of their children.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…Lipchock and colleagues (86) hypothesized that bitter-taste sensitivity might impact children's willingness to accept liquid forms of medications. Children who had at least one bitter-sensitive allele at TAS2R38 reported being more likely to reject liquid medications (97) and were more likely to have consumed solid medication forms (i.e., pills or capsules) (86) compared to children with bitter-insensitive genotypes. Determining the most effective methods of blocking bitter taste in children's medications to improve palatability and compliance is a public health priority.…”
Section: Bitter-tasting Medicationsmentioning
confidence: 99%
“…Lipchock and colleagues (86) hypothesized that bitter-taste sensitivity might impact children's willingness to accept liquid forms of medications. Children who had at least one bitter-sensitive allele at TAS2R38 reported being more likely to reject liquid medications (97) and were more likely to have consumed solid medication forms (i.e., pills or capsules) (86) compared to children with bitter-insensitive genotypes. Determining the most effective methods of blocking bitter taste in children's medications to improve palatability and compliance is a public health priority.…”
Section: Bitter-tasting Medicationsmentioning
confidence: 99%
“…10,27 For oral medications, taste is a major reason children refuse medications overall. 2,3,28 Evaluating taste and palatability of psoriasis treatments in pediatric clinical trials may help clinicians address adherence issues. In our study, most patients found the taste of the apremilast tablet acceptable, and the high compliance rate observed is promising.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the paediatric use of off-label and unlicensed medicines are a reality and that there is a lack of medicines well studied for children. Although there are already some studies focusing on the perceptions of children [26][27][28], it is still important to improve our knowledge in this area. It is fundamental to develop research in order to understand attitudes and preferences of children and their caregivers with the aim of developing dosage forms and formulations which are children-friendly.…”
Section: Final Remarksmentioning
confidence: 99%